The Correlation Of Preeclampsia, Age, And Type Of Delivery In Postpartum Hemorrhage - Kedaton, Rafi Andyah Arum; Ruspita, Mimi; Putri, Hanifa Andisetyana (Jurnal Riset Kesehatan, 2023)
The number of maternal deaths in Semarang City in 2021 was 21 cases out of 22,030 live births, or around 95.32 deaths per 100,000 live births, with the causes of death dominated by bleeding (14.29%) and hypertension (9.52%). Postpartum hemorrhage is caused by four main factors known as the 4T: tone, trauma, tissue, and thrombin. This study was conducted to determine the relationship between preeclampsia, maternal age, and type of delivery with the incidence of postpartum hemorrhage at Central General Hospital Dr. Kariadi Semarang in 2020–2022. The study was an analytic observational quantitative research with a retrospective case control study. The study was conducted in February 2023 with a total sample of 100 samples divided into case (total sampling) and control (simple random sampling) groups with a ratio of 1: 1 for each group. Statistical tests used Chi-square and odds ratio (OR) tests. The results showed that there was no relationship between preeclampsia and the incidence of postpartum hemorrhage (p-value = 0.063; OR = 0.347), there was a relationship between maternal age and the incidence of postpartum hemorrhage (p-value = 0.011; OR = 3.455), and there was a relationship between the type of delivery and postpartum hemorrhage (p-value = 0.012; OR = 2.923). The community can be expected to play an active role in integrated service post cadre activities and ante natal care assistance. Health workers and educational institutions also need to improve their knowledge and skills to form qualified health workers through certified training.